Providing Dignified Palliative Care Services in Liberia - Sonpon Blamo Sieh; Chinnie Vicky Miller Sieh; James Desmond; Catherine Machalaba (Ubiquity Press, 2019)
Background: Liberia faces a critical shortage of palliative care services, particularly for persons with advanced-stage HIV/AIDS, tuberculosis, diabetes, and cancers. Access to healthcare services is especially limited in rural areas, along with a lack of supportive social and economic resources. Home of Dignity (HoD) Health Center was established in 2013 in Yarbah's Town to fill a last-option palliative care gap. The mission emphasizes patient wellbeing and worth. HoD integrates health, agriculture, and education on-site for immediate medical needs, broader sustainable development, and reducing disease-associated stigma in local communities. Objective: We aimed to describe the Center's integrated approach and conduct a descriptive analysis of the HoD patient population. Methods: We reviewed patient characteristics (sex, age distribution, mobility status, and CD4 count on arrival) and outcomes (survival rate and community reintegration) for patients with HIV seeking care at the Center between 2013-2017. Findings: Of 182 patients (ages 3 months-50 years), over half arrived to the facility bedridden and over 82% had CD4 counts between <100-350. Of the 182 patients, 66% survived, 27% died, and 7% were lost to follow-up. Of surviving patients, 90% were successfully reintegrated into their communities. The clinic also served over 365 chronically ill patients that had been rejected by other health providers during the 2014-2015 Ebola outbreak. Conclusions: The Center is providing last-option palliative care services in the country. As a trusted healthcare center, patients also seek care for acute conditions, resulting in unanticipated resource demands. HoD's experience underscores the need for development of training programs for medical professionals, supply chains, community outreach, and resourcing channels to ensure adequate and sustainable service provision for hospice and palliative care services and reduce stigma in the country. There is an urgent need to invest in holistic palliative and overall healthcare services in Liberia.